i read the question ( given below) but couldn't understand the answer \[\large\int _{ 0 }^{ 1 }{ (\left( \prod _{ N=1 }^{ S }{ \left( x+N \right) } \right) (\sum _{ D=1 }^{ S }{ \frac { 1 }{ (x+D) } ) } )dx }\] in the answer it was asked to assume (x+1)(x+2)........(x+s)=e^t such take we can take log both sides and differentiate such that \[\large\sum _{ D=1 }^{ S }{ \frac { 1 }{ (x+D) } ) } )dx = dt\] but how is this assumption (x+1)(x+2)........(x+s)=e^t possible ????

## Comments

There are no comments in this discussion.